2013
DOI: 10.1371/journal.pone.0060416
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of HRSV in Belgium: From Multiple Genotype Circulation to Prolonged Circulation of Predominant Genotypes

Abstract: Molecular surveillance of HRSV in Belgium for 15 consecutive seasons (1996–2011) revealed a shift from a regular 3-yearly cyclic pattern, into a yearly alternating periodicity where HRSV-B is replaced by HRSV-A. Phylogenetic analysis for HRSV-A demonstrated the stable circulation of GA2 and GA5, with GA2 being dominant over GA5 during 5 consecutive seasons (2006–2011). We also identified 2 new genotype specific amino acid mutations of the GA2 genotype (A122 and Q156) and 7 new GA5 genotype specific amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 45 publications
9
37
0
Order By: Relevance
“…1B that genotype dominance has alternated in different time periods. While several genotypes cocirculated most of the time with alternating dominance, the GA2 genotype has become almost exclusive since 2005, as reported in several studies (30,33) and observed with recent viruses from Madrid and Panama (Fig. 2).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…1B that genotype dominance has alternated in different time periods. While several genotypes cocirculated most of the time with alternating dominance, the GA2 genotype has become almost exclusive since 2005, as reported in several studies (30,33) and observed with recent viruses from Madrid and Panama (Fig. 2).…”
Section: Discussionsupporting
confidence: 68%
“…Recent publications have drawn attention to the shift from "multiple genotype circulation to prolonged circulation of predominant genotypes," as seen in Belgium between 1996 and 2011 (30). In addition, a novel GA2 variant with a 72-nt duplication, named ON1 and first detected in Ontario (Canada) in December 2010 (31), has spread rapidly worldwide (32)(33)(34), exacerbating the current dominance of the GA2 genotype.…”
Section: Evolution and Dominance Of Group A Genotypes Over Timementioning
confidence: 99%
“…[29]. The interplay of pre-existing immunity in the community and the genetic and antigenic properties of the RSV virus to evade the immune response may explain changes in genotype dominance over time [30]. The predominance of RSV-A viruses has been attributed to increased variability among RSV-A strains [30].…”
Section: Distribution Of Rsv Genotypesmentioning
confidence: 99%
“…The interplay of pre-existing immunity in the community and the genetic and antigenic properties of the RSV virus to evade the immune response may explain changes in genotype dominance over time [30]. The predominance of RSV-A viruses has been attributed to increased variability among RSV-A strains [30]. Based on the fact that the dominant strains shift yearly, evasion of immunity induced by previous strains may be a mechanism for re-infection [31].…”
Section: Distribution Of Rsv Genotypesmentioning
confidence: 99%
See 1 more Smart Citation